Cytotoxic and potential anticancer constituents from the stems of Schisandra pubescens. (September 2013) - Lu, Yan; Li, Yu-Quan; Liu, Yi-Nan; Lee, Kuo-Hsiung; Chen, Dao-Feng
Abstract Context: The diethyl ether extract of the stems of Schisandra pubescens Hemsl. et Wils. (Schisandraceae) was found to exhibit cytotoxic activity in vitro. However, investigations of the bioactive constituents of this plant have been very limited. Objective: Elucidation of the cytotoxic constituents of S. pubescens was performed. Methods: Repeated silica gel column chromatography and preparative TLC were used for the chemical investigation of the diethyl ether extract of S. pubescens stems. All isolates were evaluated for their in vitro cytotoxicity against A549, PC-3, KB and KBvin human cancer cell lines. Results: Nine known compounds were obtained, including four lignans, epischisandrone (1), tigloylgomisin P (2), cagayanone (3) and (−)-gomisin L2 (4), together with five triterpenoids, micranoic acid B (5), lancifodilactone H (6), coccinic acid (7), schisanlactone B (8) and anwuweizonic acid (9). Compounds 2–6 and 8 showed moderate to marginal cytotoxicity, with GI50 values of 11.83–35.65 μM. Conclusion: The isolation of 1–9 from S. pubescens and the cytotoxicities of 3–6 are first reported. Compounds 2–6 and 8 could be the active principles responsible for the anticancer effects of S. pubescens.